Gameization of Educational Process in the Assessments of Students and Teachers - V. A. Sagaidak; A. L. Kuzevanova; A. N. Kapshuk (Высшее образование в России)
The article is devoted to the study of significance, role and potential risks of the gameization of educational processes in higher education institutions in the context of digital transformation of society and the emergence of new requests to educational organizations. The purpose of the study is to identify the features of students’ and teachers’ perception of the existing practice of gameization of educational processes. The article presents the results of online questionnaire survey of students of the Volgograd Institute of Management and a series of expert interviews with representatives of the teaching staff. The results of the study indicate a high prevalence of the practice of gamification and its positive perception by the most participants in the educational process. The key effects of integrating game elements include increasing educational motivation and the quality of professional training, ensuring that the educational process meets the requirements of relevance. Among the main limitations in the implementation of gameization, teachers indicate the need to maintain a balance of classes in game and traditional forms, as well as the presence of specific disciplines and thematic blocks that are available for presentation exclusively in the classical format. At the same time, the main risk of introducing gameization, in particular competitive elements, is associated with the development of negative socio-psychological phenomens at the level of students and student groups in general. This conclusion is consistent with the results of student questionnaire survey. The disordered nature of the gameization of educational process revealed by the results of the study reflects the general trends of educational organizations and conditioned by the low level of motivational, cognitive, organizational and methodological readiness of teachers to carry out such innovative activities. The limiting organizational and managerial factor is the lack of consolidation of game forms of classes in the work programs of disciplines. The authors’ recommendations on expanding the practice of gameization of educational process are related to methodological support and professional development of teachers in the context of modern gaming and digital educational technologies and resources, stimulating activities for the development and implementation of game-based courses, and the consolidation of game forms of classes in discipline programs.